Understanding the collaborative assessment identity of English for academic purposes practitioners in higher education - Levrai, Peter; García Mayo; María del Pilar (Elsiver, 2026)
Collaboration is a valued learning outcome in Higher Education (HE) and students are likely to encounter collaborative assignments, such as a group essay or oral presentation, during their studies. While there are positive affordances to these types of assignments, their summative assessment may often represent a problematic area. In order to better understand the assessment practices of English for Academic Purposes (EAP) practitioners toward collaborative writing, a constructivist Grounded Theory approach was followed. Twenty practitioners were asked to evaluate four different models of collaborative assessment. In-depth discussion of these approaches highlighted the concerns and beliefs of EAP practitioners when it comes to collaborative assignments, with the key principles impacting practitioners’ approach to collaborative assessment being fairness, transparency and simplicity. These in turn shaped three guiding orientations: reward, practical and defensibility. Understanding what guides teachers in collaborative assessment gives us the opportunity for training and professional development to enable more principled and consistent collaborative assessment practices.